Representasi Han dalam Drama Mystic Pop-Up Bar - Nurjanah, Sindy Novi; Young, Hwang Who (Universitas Gadjah Mada, 2023)
Han (한恨) is a complicated Korean sociocultural concept which related to unresolved resentment, pain, grief, and anger. This han concept is often used in Korean cultural productions, for instance JTBC Korean drama, “Ssanggappocha (쌍갑포차), Mystic Pop-up Bar (MPUB)”. It tells about the characters’ han stories along with the process of how they resolve it. Therefore, this research used MPUB drama as research object to see the representation and finding the types of han. The theory used in this research is Andrew Sung Park’s theory (1993) about the structure of han. This research uses a qualitative descriptive method to analyze the data which is the dialogues of related scenes. The result of this research is out of nine forms of han according to Park, there are five forms of han discovered in the drama. Those forms are: (1) the han of individual: conscious-passive; (2) the han of individual: unconscious-active; (3) the han of individual: unconscious-passive; (4) the han of group: unconscious-passive; and (5) the han of nature. Generally, the dominant form found in the drama is han of individual expressed in passive way since the characters showed their process of accepting the han rather than being aggressive toward it.